2010
DOI: 10.1111/j.1462-2920.2009.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptomycetes contributing to atmospheric molecular hydrogen soil uptake are widespread and encode a putative high‐affinity [NiFe]‐hydrogenase

Abstract: Uptake of molecular hydrogen (H2) by soil is a biological reaction responsible for approximately 80% of the global loss of atmospheric H2. Indirect evidence obtained over the last decades suggests that free soil hydrogenases with an unusually high affinity for H2 are carrying out the reaction. This assumption has recently been challenged by the isolation of Streptomyces sp. PCB7, displaying the high-affinity H2 uptake activity previously attributed to free soil enzymes. While this finding suggests that actinob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
197
4
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(217 citation statements)
references
References 52 publications
(92 reference statements)
13
197
4
3
Order By: Relevance
“…We definitively confirm that group 5 [NiFe] hydrogenases can mediate high-affinity H 2 oxidation and provide strong support for the hypothesis that these enzymes are the principal sinks for atmospheric H 2 . The kinetic parameters of whole-cell H 2 oxidation by Hyd2, as observed in isolation in the Δhyd13 strain and deleted in the Δhyd2 strain, are very similar to the high-affinity processes observed in whole soil samples (9, 10) and cultured streptomycetes (12,15) (Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…We definitively confirm that group 5 [NiFe] hydrogenases can mediate high-affinity H 2 oxidation and provide strong support for the hypothesis that these enzymes are the principal sinks for atmospheric H 2 . The kinetic parameters of whole-cell H 2 oxidation by Hyd2, as observed in isolation in the Δhyd13 strain and deleted in the Δhyd2 strain, are very similar to the high-affinity processes observed in whole soil samples (9, 10) and cultured streptomycetes (12,15) (Fig. 4).…”
Section: Discussionsupporting
confidence: 51%
“…It is proposed that group 5 [NiFe] hydrogenases are responsible for high-affinity H 2 oxidation in streptomycetes (12,17). The genes encoding this newly discovered hydrogenase lineage (hhyLS) are highly conserved and taxonomically restricted; among sequenced genomes, this hydrogenase is only widespread in environmental actinomycetes, including Streptomyces, Mycobacterium, Rhodococcus, and Frankia species (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently shown that some aerobic soil actinobacteria and acidobacteria persist by scavenging H 2 from the lower atmosphere (Constant et al, 2010;Greening et al, , 2015a, overturning long-held beliefs that hydrogen metabolism is restricted to low O 2 , high H 2 environments and highlighting the importance of H 2 for survival in addition to growth . Biochemists have simultaneously elucidated mechanisms dependent on reversed electron flow that enable certain hydrogenases to function in the presence of the oxygen (traditionally an inhibitor of their active sites) (Fritsch et al, 2011;Shomura et al, 2011;Horch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%